2020
DOI: 10.3390/ijms21031035
|View full text |Cite
|
Sign up to set email alerts
|

The Demonstration of an Aqp4/Tgf-Beta 1 Pathway in Murine Astrocytes Holds Implications for Both Neuromyelitis Optica and Progressive Multiple Sclerosis

Abstract: The role exerted by Aquaporin 4 (AQP4) as a regulator of astrocyte immune functions has been poorly explored. A recent report demonstrates that under neuroinflammatory conditions, the expression of Aqp4 on murine astrocytes is mandatory for the effective control of acute inflammation in the central nervous system. Such an immunomodulatory function appears to be mediated by a promotion of the transforming growth factor beta 1 (Tgfb1) pathway. Here, these results are discussed in the context of neuromyelitis opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Alternatively, these data may reflect differences in the microenvironment upon demyelination. Indeed, demyelination changes the expression of several growth factors, including fibroblast growth factor and transforming growth factor b1 (Huang and Dreyfus, 2016), which can regulate Gli2 expression (Brewster et al, 2000;Javelaud et al, 2011) and astrocyte generation (Nataf, 2020;Savchenko et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, these data may reflect differences in the microenvironment upon demyelination. Indeed, demyelination changes the expression of several growth factors, including fibroblast growth factor and transforming growth factor b1 (Huang and Dreyfus, 2016), which can regulate Gli2 expression (Brewster et al, 2000;Javelaud et al, 2011) and astrocyte generation (Nataf, 2020;Savchenko et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, it was found that the serum from patients with NMO contains autoantibodies directed against the astrocytic protein aquaporin 4 (AQP4) [59]. More recently, it was suggested that these antibodies can interfere with the systemic and intra-cerebral synthesis of transforming growth factor β1 (TGF-β1), thus abolishing an important anti-inflammatory response [60].…”
Section: Discussionmentioning
confidence: 99%